Strengthening Agricultural Credit Performance: The Moderating Role of Credit Collateral on the Relationship Between Working Capital Loans and Bad Loan Risk in Farmer Groups - Antonius Yohanes William Timuneno; Maria Goreti Malut (LP2M IAIN Palopo, 2026)
Strengthening agricultural credit performance: the moderating role of credit collateral on the relationship between working capital loans and bad loans risk in farmer group. Purpose: This study explores how credit collateral moderates working capital loans to minimize bad loans risk among farmers. This study employes a quantitative research design using Smart PLS 4.1 as the analytical tool for inferential statistical testing. The reduced risk of non-performing loans is influenced by structured working capital system’s and significally using credit collateral. This study higlights farmer group with unstructured working capital credit schemes and seeks to reposition credit collateral as key in reducing default risk. Improving credit Effectiveness through the optimalization of credit collateral within the credit mechanism